Transporting People with Visual Impairments: Knowledge of University Campus Public Transportation Workers. (March 2019) - Fast, Danene K.; Wild, Tiffany A.
Introduction: To support independent travel skills and accessibility for people with visual impairments (i.e., those who are blind or have low vision), this research acknowledges bus driver perceptions of visual impairment and investigates how bus drivers interact with visually impaired travelers who ride public transportation. Methods: This study utilized the Social Responsibility about Blindness Scale and a researcher-created instrument to explore how bus drivers interact with visually impaired travelers. Results: Fifty-five drivers participated in this study, with 94.55% of these drivers reporting that they have had experiences interacting with visually impaired passengers. The top concern drivers reported was ensuring these passengers located the correct stop (26.56%). Using Likert-type scale ratings to assess driver knowledge and role in assisting passengers with vision loss, overall mean average of driver knowledge was 3.33 ( SD = 1.09, V = 1.23), indicating, as a whole, driver knowledge was in the range of "unsure/don't know." Discussion: Although many campus area bus drivers have experience interacting with passengers who are visually impaired, the attitude of drivers toward visual impairment is varied, and their knowledge of visual impairments is limited. Implications for practitioners: Based on results, drivers recognize that accommodations may be needed for passengers with vision loss, and they have an interest in learning how to assist passengers who are visually impaired who ride campus transportation. Based on this outcome, in-service training for drivers to address interactions and accommodations for passengers with vision loss may be warranted within public transportation operations.